Distinct binding and immunogenic properties of the gonococcal homologue of meningococcal factor h binding protein. - Jongerius, I; Lavender, H; Tan, L; Ruivo, N; Exley, R; Caesar, J; Lea, S; Johnson, S; Tang, C (Public Library of Science, 2013)
Neisseria meningitidis is a leading cause of sepsis and meningitis. The bacterium recruits factor H (fH), a negative regulator of the complement system, to its surface via fH binding protein (fHbp), providing a mechanism to avoid complement-mediated killing. fHbp is an important antigen that elicits protective immunity against the meningococcus and has been divided into three different variant groups, V1, V2 and V3, or families A and B. However, immunisation with fHbp V1 does not result in cross-protection against V2 and V3 and vice versa. Furthermore, high affinity binding of fH could impair immune responses against fHbp. Here, we investigate a homologue of fHbp in Neisseria gonorrhoeae, designated as Gonococcal homologue of fHbp (Ghfp) which we show is a promising vaccine candidate for N. meningitidis. We demonstrate that Gfhp is not expressed on the surface of the gonococcus and, despite its high level of identity with fHbp, does not bind fH. Substitution of only two amino acids in Ghfp is sufficient to confer fH binding, while the corresponding residues in V3 fHbp are essential for high affinity fH binding. Furthermore, immune responses against Ghfp recognise V1, V2 and V3 fHbps expressed by a range of clinical isolates, and have serum bactericidal activity against N. meningitidis expressing fHbps from all variant groups.